2018
DOI: 10.1111/ajt.15025
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of organ donation registration

Abstract: Rates of organ donor registration range from 20% to 60% throughout the United States. The purpose of this study was to examine sociogeographic differences in organ donor registration rates throughout Missouri to identify varying patterns The organ donor registration rate from each Department of Motor Vehicle office in Missouri was extracted from the National Organ Registration database, office locations were geocoded, and census tract level sociodemographic characteristics were extracted. Spatial regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 14 publications
1
23
0
2
Order By: Relevance
“…Of note, in our multivariable analyses that included both the socioeconomic deprivation index and the racial ICE, the effect of racial ICE was decreased; suggesting that the effect of racial ICE on organ donor registration may be mediated, in part, by socioeconomic deprivation. Although most previous studies focused on individual determinants of organ donor registration, 6,7,12,33 these data add to our limited understanding of contextual, geospatial determinants of organ donor registration 15‐17 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, in our multivariable analyses that included both the socioeconomic deprivation index and the racial ICE, the effect of racial ICE was decreased; suggesting that the effect of racial ICE on organ donor registration may be mediated, in part, by socioeconomic deprivation. Although most previous studies focused on individual determinants of organ donor registration, 6,7,12,33 these data add to our limited understanding of contextual, geospatial determinants of organ donor registration 15‐17 …”
Section: Discussionmentioning
confidence: 99%
“…Such public health interventions have successfully been applied to infectious disease and cancer surveillance 43‐45 . Previous studies utilizing state BMV data have only been single state 11,15‐17,46 and may not be generalizable. That this study identified population‐level metrics strongly associated with organ donor registration across multiple, diverse states is a step closer toward implementing similar though novel strategies to improve organ availability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous organ donation studies have been conducted in Western countries targeting Caucasian populations (Dahl et al, 2019; Moloney et al, 2019), as well as, specific ethnic populations such as African Americans (Shacham et al, 2018) and Hispanics (Salim et al, 2011). Yet, a significant gap in knowledge exists with regards to publishable research on organ donation within the Middle Eastern context.…”
Section: Introductionmentioning
confidence: 99%
“…Disparities in race/ethnicity, age, education, marriage, religious beliefs, and immigrant acculturation have been explored in the literature for organ donor registration and authorization of donors. 4 9 While much of the literature focuses on maximizing organ donor registration and identifying key demographic factors that explain variation in authorization and donor registration decisions, 10 –12 these studies do not directly address the differences in populations served by each OPO and the unique challenges that they may face. This study aims to address this gap by considering the general circumstances of the population within each DSA.…”
Section: Introductionmentioning
confidence: 99%